Neurodevelopmental outcomes after prenatal exposure to lamotrigine monotherapy in women with epilepsy: a systematic review and meta-analysis - Audrey Peron; Cyndie Picot; Lucie Jurek; Mikaïl Nourredine; Emmanuelle Ripoche; Priscilla Ajiji; Michel Cucherat; Judith Cottin (BMC, 2024)
Abstract Background Lamotrigine has become one of the most commonly prescribed antiseizure medications (ASM) in epileptic women during pregnancy and therefore requires regular updates regarding its safety. The aim of this study was to estimate the association between in utero exposure to lamotrigine monotherapy and the occurrence of neurodevelopmental outcomes. Methods All comparative studies assessing the occurrence of neurodevelopmental outcomes after epilepsy-indicated lamotrigine monotherapy exposure during pregnancy were searched. First, references were identified through a snowballing approach, then, through electronic databases (Medline and Embase) from 2015 to June 2022. One investigator evaluated study eligibility and extracted data and a second independent investigator reviewed the meta-analysis (MA). A systematic review and random-effects model approach were performed using a collaborative WEB-based meta-analysis platform (metaPreg.org) with a registered protocol (osf.io/u4gva). Results Overall, 18 studies were included. For outcomes reported by at least 4 studies, the pooled odds ratios and 95% confidence interval obtained with the number of exposed (N1) and unexposed children (N0) included were: neurodevelopmental disorders as a whole 0.84 [0.66;1.06] (N1 = 5,271; N0 = 22,230); language disorders or delay 1.16 [0.67;2.00] (N1 = 313; N0 = 506); diagnosis or risk of ASD 0.97 [0.61;1.53] (N1 = at least 5,262; N0 = 33,313); diagnosis or risk of ADHD 1.14 [0.75;1.72] (N1 = at least 113; N0 = 11,530) and psychomotor developmental disorders or delay 2.68 [1.29-5.56] (N1 = 163; N0 = 220). The MA of cognitive outcomes included less than 4 studies and retrieved a significant association for infants exposed to lamotrigine younger than 3 years old but not in the older age groups. Conclusion Prenatal exposure to lamotrigine monotherapy is not found to be statistically associated with neurodevelopmental disorders as a whole, language disorders or delay, diagnosis or risk of ASD and diagnosis or risk of ADHD. However, the MA found an increased risk of psychomotor developmental disorders or delay and cognitive developmental delay in less than 3 years old children. Nevertheless, these findings were based exclusively on observational studies presenting biases and on a limited number of included children. More studies should assess neurodevelopmental outcomes in children prenatally exposed to lamotrigine.